Systematic Literature Review: The Implementation of Gamification in Mathematics Learning at Primary Schools - Tonioka, Nadya Hesty; Sutopo, Yeri; Ellianawati, Ellianawati; Kurniawan, Yunda; Avrilianda, Decky (Papanda Publisher, 2025)
Mathematics education at the primary level faces significant challenges in maintaining student engagement and motivation, particularly with traditional teacher-centered approaches. Gamification, defined as the application of game elements to non-game educational contexts, has emerged as a promising solution to enhance mathematics learning outcomes. However, systematic examination of gamification research trends and effectiveness in primary mathematics education remains limited. This systematic literature review analyzed 15 peer-reviewed articles published between 2020 and 2025 focusing on gamification implementation in primary school mathematics education. Articles were systematically searched using Google Scholar with keywords